Católicos carismáticos e as eleições municipais de 2012 - Júlia Miranda (Ciências Sociais Unisinos)
The 2012 local polls have revealed a new Catholic way to participate in the electoral process. The novelty lies in the candidacy of vowed members of the local Charismatic community. This article analyses four of these unprecedented candidacies and sets out to show their differentiated and extensive – almost exclusive – use of social networks as a campaigning tool. It highlights how this new way of doing Politics (a) maintains a close affinity with the organisation and the communal lives led by this segment of the Catholic faith; and (b) offers new perspectives from which to analyse their political participation in local and national elections, including the creation of its own political category, the “charismatic candidate”. In the 2012 elections in the city of Fortaleza, among the main characteristics of these novel candidacies was the use of online communication – especially via tools such as Twitter, Facebook, and YouTube channels; which resulted in increased visibility and opened up the possibility to closely observe the interactions and the sharing of meanings between the religious candidates and their virtual followers. We analyse this negotiation of meanings, its peculiar dynamics and what it represents in the context of political and religious practices within an urban environment.